‘Happy’ Hipoksemia pada pasien COVID-19 - Dita Ayu Permata Dewi; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2021)
One of the dubious aspects for a doctor who treats COVID-19 patients with patients who have experienced hipoxia, but without the proper signs of respiratory distress, even the absence of complaints of shortness of breath. This phenomenon is referred to as ‘happy hipoxia’. For doctors, the presence of ‘happy hipoxia’ in a Covid-19 patient, even though the patient is in a hypoxemic state, can mistakenly lead to the message that the patient is not in a critical condition and is fine. These cases can rapidly skip the clinical evolutionary stage and develop Acute Respiratory Distress syndrome (ARDS), with cardiac and respiratory attacks simultaneously leading to sudden death. Pulse oximetry should be interpreted with caution, as the oxyhemoglobin dissociation curve shifts to the left. The pathophysiology of ‘happy hipoxia’ can be accepted by the hypothesis that neurological factors are involved. Hypoxia usually activates carotid body chemoreceptors, and afferent signals are transmitted through the nucleus tractus solitarius. This usually causes an increase in the respiratory rate and sensation of dyspnea. SARS-CoV-2 infects the brain via the olfactorial bulb and olfactory nerves, via trans-synaptic spread, eventually reaching the brain stem, and the nucleus tractus solitarius. Inflammation of the nucleus solitarius tract by viral invasion that stimulates afferent hypoxia from the carotid body may not be transmitted effectively to the nucleus solitarius tract, resulting in impaired efferent respiratory response. This explains why COVID-19 patients exhibit near normal breathing in the presence of severe hipoxia (Happy hypoxia). The clinician must not only trust a patient who appears ‘happy’ but must also trust the respiratory rate, signs of hyperventilation, oxygen saturation, and invasive measurements of hipoxia / hypocapnia at regular time intervals.